Existence of Banjar Tradition Arts in Islamic Era in South Kalimantan - Huriyah Huriyah; Sri Normuliati (Departement of History and Islamic Civilization, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2022)
Until now Malay art with Islamic nuance is still maintained by the people of South Kalimantan. The development of Malay art is largely influenced by the outside, but does not leave the main elements of the art. The tradition of Malay culture during the Islamic era in South Kalimantan blended with the locality of the Banjar community as found in fine arts, oral literary arts, music, sound arts, dance, theater and handicraft arts. The purpose of this research is to know the art traditions of the Banjar community during the Islamic era in South Kalimantan and to know how the existence of the Banjar community art traditions during the Islamic era in South Kalimantan. In this study using the method of library research is a method of collecting library data from research activities conducted. Research conducted using the literature method is a way to obtain data in the form of relevant information sourced from books, documents, or historical account records. Based on information that has been obtained various Banjar community art traditions during the Islamic era in South Kalimantan, namely building art, carving, painting, lamut, madihin, mamanda, tarbang ampat, and rudat dance. Based on relevant references, the existence of Banjar community art traditions during the Islamic era in South Kalimantan still continues to exist and continues to this day, namely carving with the creed, painting for sasirangan, lamut, madihin and mamanda patterns, the use of tarbang ampat as a companion to the kasidah burdah, and rudat dance which is a form of praise to the Prophet Muhammad.